Numerical Simulation of Concentration Over-voltage in a Polymer Electrolyte Fuel Cell under Low-Hydrogen Conditions - Yamamoto, Takahisa; Ishimaru, Kazuhiro; Osman, Kahar; Kori, Mohamad Ikhwan; Khudzari, Ahmad Zaharan; Yamamoto, Tsuyoshi (International Journal of Integrated Engineering, 2018)
This article elucidates the effect of low hydrogen concentration fuel gas on polymer electrolyte fuel cell (PEFC) performance, with particular emphasis on the transport of chemical species in the anode separator channel and the electrochemical reactions. A numerical simulation model for PEFCs was developed; the model combined a computational fluid dynamics model for mass transfer in the anode separator and the gas diffusion layer (GDL) as well as a PEFC electrochemical reaction model taking into account the activation, concentration, and resistance over-voltages. The emphasis in this study is placed on obtaining a basic understanding of how three-dimensional flow and low-hydrogen fuel transport phenomena in the anode separator channel impact the electrochemical processes occurring in PEFCs. Comparison of the numerical simulation results with experimental data indicates that the performance degradation in PEFCs is negligible for hydrogen concentrations over 30%, whereas it becomes significant for concentrations below 10%. Furthermore, the numerical simulation results show that controlling the fuel supply flow rate stimulates hydrogen transport in the GDL and the catalyst layer, which consequently enhances PEFC performance under low-hydrogen conditions.